Pola Pembinaan Umat Buddha oleh Pandita Magabudhi di Kota Tangerang - Lalita Vistari Satyananda Wiryana Dharma (STABN Sriwijaya, 2019)
The problem raised in this research was the decreased quantity of Buddhists in the small town of Tangerang, in fact is caused by the due of lack of knowledge or beliefs some Buddhists in Tangerang, or less maximum construction of Buddhists by the Pandita in Tangerang. The purpose of this study was to describe the pattern of construction of the Buddhists in Tangerang, which in terms of it; the researcher used descriptive qualitative approach. The subject of the research is the Buddhist, monasteries, and Pandita Magabudhi in Tangerang. The object of the research was the pattern of the construction of the Buddhists. The technique used is the notes, by means of observation, interviews, and documentation. The instruments of data collection are as follow: the form of guidelines, guidelines for observation, interviews, and observation. The researches used data analysis of Milles and Huberman, namely data collection, data reduction, data presentation, and conclusions. Based on the results of the study the researcher concludes that the patterns of construction performed by the Pandita Magabudhi in Tangerang are proactive with the construction of the informative-educational, consultative, and advocative. This can be seen by the presence of regular coaching to the monasteries and chedis in the shade of the Magabudhi in the form of construction of the informative, as a Dharmaduta delivery each month. Second, the construction of the education conducted by the Pandita by providing education on how to do the service of the death, the Ministry of reading Paritta for sick people, wedding services, service worship together. Third, the advocative coaching or counseling for people who have problems in the Dhamma or the problems in his/her household with the giving of advice.Masalah yang diangkat dalam penelitian ini adalah menurunnya jumlah umat Buddha di beberapa wihara di daerah Tangerang, yang sebenarnya disebabkan oleh kurangnya pengetahuan atau kepercayaan umat pada ajaran agama Buddha di daerah Tangerang, atau kurang maksimalnya pembinaan umat Buddha oleh pandita di Tangerang. Tujuan penelitian ini untuk menggambarkan pola pembinaan umat Buddha oleh pandita Magabudhi di Tangerang, yang dalam hal ini, peneliti menggunakan pendekatan deskriptif kualitatif. Subjek penelitian adalah umat Buddha, wihara-wihara, dan Pandita Magabudhi di kota Tangerang. Objek penelitian adalah pola pembinaan umat Buddha. Teknik yang digunakan adalah nontes, dengan cara observasi, wawancara, dan dokumentasi. Instrumen pengumpulan data adalah sebagai berikut: bentuk-bentuk pedoman, pedoman observasi, pedoman wawancara, dan dokumentasi. Penelitian ini menggunakan analisis data Miles dan Huberman pengumpulan data secara koleksi data, reduksi data, penyajian data, dan kesimpulan. Berdasarkan hasil penelitian, peneliti menyimpulkan bahwa pola pembinaan yang dilakukan oleh Pandita Magabudhi di Tangerang proaktif dengan pembinaan informatif, yaitu pendidikan, konsultatif, dan advokasi. Hal ini dapat dilihat dengan adanya pembinaan reguler ke wihara-wihara dan cetiya di bawah naungan Magabudhi dalam bentuk pembinaan informatif, sebagai pengiriman Dharmaduta setiap bulan. Kedua, pembangunan pendidikan yang dilakukan oleh pandita dengan memberikan pendidikan tentang melakukan pelayanan kematian, layanan bagi orang sakit, layanan pernikahan, layanan ibadah bersama. Ketiga, pembinaan advokasi atau konseling untuk orang-orang yang memiliki masalah dalam Dhamma atau masalah dalam rumah tangganya dengan pemberian nasihat.